I know diamonds I think don't you have to divide
1.4565 * 10 ^ - 5
I would really really appreciate it if you marked me as brainiest ☆〜(ゝ。∂)
Answer:
C
Step-by-step explanation:
Given
(3x + 7)(2x - 6)
Each term in the second factor is multiplied by each term in the first factor, that is
3x(2x - 6) + 7(2x - 6) ← distribute both parenthesis
= 6x² - 18x + 14x - 42 ← collect like terms
= 6x² - 4x - 42 → C
Answer:
x=53
Step-by-step explanation:
pythagoras theorem
a^2 + b^2 =c^2
here a and b are two small sides and c is hypotenuse (longest side)
28^2 + 45^2 = c^2
784 + 2025 =x^2
2809 =x^2
=x
53 =x